'You can't sit with us:' Gender and the differential roles of social intelligence and peer status in adolescent relational aggression. (March 2016) - Loflin, Della C.; Barry, Christopher T.
Abstract: Despite common notions that relational aggression (i.e., gossip, rumors, manipulation targeting another's social status; Crick & Grotpeter, 1995) is most commonly exhibited by females, there is mixed evidence regarding gender differences and what factors might heighten gender-specific risk for adolescent relational aggression (RA). The present study considered perceived social intelligence and peer status as such factors. Participants were 258 adolescents (217 males, 41 females) ranging in age from 16 to 19 attending a residential program for youth who have dropped out of school. Males and females did not differ on RA according to self-report or peer nominations. Self-reported social intelligence was associated with higher self-reported RA but only for females. The implications for future research as well as efforts for understanding RA are discussed. Highlights: Examined adolescent social intelligence, peer status, and relational aggression Extended prior research by focusing on self-perceptions of social intelligence Social intelligence predicted higher relational aggression for females.